Milder operating parameters for one-step conversion of fructose to levulinic acid over sulfonated H-beta zeolite in aqueous media - Bisen, Swapneel K.; Niphadkar, Prashant S.; Nandanwar, Sachin U.; Simakova, Irina; Bokade, Vijay V. (Environmental Progress & Sustainable Energy, 2021)
The sulfonated H-beta zeolite was successfully prepared and used for the synthesis of levulinic acid (LA) fromD-fructose. The catalyst was characterized by powder X-ray diffraction, Fourier transform infrared spectroscopy, scanning electron microscope, N-2 physisorption, NH3-temperature programmed desorption and carbon-hydrogen-nitrogen-sulfur analysis. The total acid amount is increased with increase in sulfur loading, confirmed that the sulfonic acid group (SO3-H) is successfully grafted onto zeolite structure. The various parameters such as different amount of sulfur loading, reaction temperature, time, catalyst loading was studied for selective production of LA. The catalytic activity of sulfonated H-beta (S-beta) zeolite was found to be efficient for synthesis of LA from D-fructose in aqueous media. Maximum LA yield of 43.5 mol%, low HMF yield (<1%) with 98.15% fructose conversion was obtained with 3% S-beta catalyst at 160 degrees C for 7 hr. The catalyst was reusable for minimum three times by H2O2 regeneration. This study provides the new zeolitic catalyst for the efficient production of LA at shorter reaction time (7 hr) and low catalyst to substrate ratio (0.7:1).
Keywords: conversion; D-fructose; H-beta; HMF; levulinic acid; sulfonated zeolite; yield

Milder operating parameters for one-step conversion of fructose to levulinic acid over sulfonated H-β zeolite in aqueous media - Bisen, Swapneel K.; Niphadkar, Prashant S.; Nandanwar, Sachin U.; Simakova, Irina; Bokade, Vijay V. (Environmental Progress & Sustainable Energy, 2021)
Abstract The sulfonated H-β zeolite was successfully prepared and used for the synthesis of levulinic acid (LA) from D-fructose. The catalyst was characterized by powder X-ray diffraction, Fourier transform infrared spectroscopy, scanning electron microscope, N2 physisorption, NH3-temperature programmed desorption and carbon–hydrogen–nitrogen–sulfur analysis. The total acid amount is increased with increase in sulfur loading, confirmed that the sulfonic acid group (SO3-H) is successfully grafted onto zeolite structure. The various parameters such as different amount of sulfur loading, reaction temperature, time, catalyst loading was studied for selective production of LA. The catalytic activity of sulfonated H-β (S-β) zeolite was found to be efficient for synthesis of LA from D-fructose in aqueous media. Maximum LA yield of 43.5 mol%, low HMF yield (<1%) with 98.15% fructose conversion was obtained with 3% S-β catalyst at 160°C for 7 hr. The catalyst was reusable for minimum three times by H2O2 regeneration. This study provides the new zeolitic catalyst for the efficient production of LA at shorter reaction time (7 hr) and low catalyst to substrate ratio (0.7:1).
Keywords: conversion; D-fructose; H-β; HMF; levulinic acid; sulfonated zeolite; yield

Rhizobacterial consortium mediated aroma and yield enhancement in basmati and non-basmati rice ( Oryza sativa L.) - Dhondge, Harshal V.; Pable, Anupama A.; Barvkar, Vitthal T.; Dastager, Syed G.; Nadaf, Altafhusain B. (Journal of Biotechnology, 2021)
Basmati and non-basmati rice varieties are commercially important. Aromatic rice varieties are low yielding and recently depletion in aroma is observed due to the shift towards modern agriculture. Therefore, it is necessary to restore the aroma and increase the yield through sustainable agriculture. The use of microbial bioinoculants is one of the promising ways to achieve these targets. With these objectives, rhizospheric bacterial strains Enterobacter hormaechei (AM122) and Lysinibacillus xylanilyticus (DB25) having the property of synthesizing 2acetyl-1-pyrroline (2AP) were isolated from the rhizosphere of two aromatic rice varieties, Ambemohar-157 and Dehradun Basmati respectively and their effect on plant growth, aroma and yield enhancement under mono-inoculation and consortium conditions was analyzed. The bacterial inoculum in consortium resulted in significant improvement in vegetative growth, yield and 2AP content over mono inoculation and control. The study highlights the potential of E. hormaechei and L. xylanilyticus in plant growth, yield and aroma enhancement in basmati and non-basmati rice varieties. These strains can be taken up further for developing a commercial bioformulation.
Keywords: 2-Acetyl-1-pyrroline; Basmati rice; Non-basmati rice; plant growth promotion; Rhizosphere; yield